Masculinities, postcolonialism and transnational memories of violent conflicts. Issue 3 (3rd July 2019) - Stoltz, Pauline
ABSTRACT: The main objective of this study is to demonstrate the advantages of combining the concept of hegemonic masculinity with a postcolonial perspective when analysing the identity formations of first and second-generation postcolonial migrants, whose gendered identities are formed by narratives of transnational memories of decolonization, war and violence. The results expand approaches to the analysis of masculinity, not only by combining masculinity with a postcolonial approach, but also by a methodological intervention into narratives of transnational memories. By including transnational and postcolonial perspectives, this study also contributes to calls to rethink masculinity from global, transnational and postcolonial perspectives (Connell, R. (2016). Masculinities in global perspectives. Theory and Society, 45, 303–318; Messerschmidt, J. (2015). Masculinities in the making . Lanham, MD: Rowman & Littlefield; Hearn, J., Blagojević, M., & Harrison, K. (eds.). (2014). Rethinking transnational men: Beyond, between and within nations . New York, NY: Routledge; Beasley, C. (2008). Rethinking hegemonic masculinity in a globalizing world. Men and Masculinities, 11, 86–103). I illustrate the argument with examples of the identity formations of postcolonial migrants from Indonesia to the Netherlands and from narratives of transnational memories of events of mass violence and human rights abuses during the Indonesian war for independence from the colonial power of the Netherlands (1945–1949). I retrieve these examples by means of a biographical narrative analysis of the Dutch autobiographical and multimodal novel 'The interpreter from Java' by Alfred Birney (2016).